Nutrition Fact Panel Use and its Association to Diet Quality among University Students in Universitas Indonesia - Christy, Sarah; Khusun, Helda; Chandra, Dian Novita; Sunardi, Diana (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
The aim of this study was to assess the association between Nutrition Fact Panel (NFP) use and diet quality among university students. A comparative cross sectional study was conducted in 2019 among 172 college students living in dormitory of Universitas Indonesia, Depok, Indonesia. Data about socioeconomic and demographic characteristics, food preparation, NFP use and nutritional knowledge were collected through interview using structured questionnaire. Nutritional status was obtained by direct height and weight measurement. Diet quality was measured using Diet Quality Index-International (DQI-I) score, derived from 3x24 hours recall. Finding of this study showed that the characteristics of NFP users and non-users were not differed significantly except for nutritional knowledge in which NFP users were 1.852 times more likely to have good knowledge than NFP non-users (p<0.05; 95% CI:1.009−3.396). The median total diet quality score was categorized as low (44 out of 100). There was no association between NFP use and total diet quality score even after controlling for possible confounder. However, the exploration in each component of diet quality measurement showed adequacy score of calcium was significantly higher in NFP users than non-users (p<0.05). NFP use also positively associated to total variety score (β=0.985; p<0.05). Future nutrition interventions could focus on enhancing the use and understanding of NFP among university students